Effectiveness of various cryotherapy systems at decreasing ankle skin temperatures and applying compression - Rigby, J. H.; Dye, S. B. (International Journal of Athletic Therapy & Training, 2017)
A variety of cryotherapy systems may be used to cool tissues immediately after an injury. The purpose our study was to examine the effect of a 30-min application of various cryotherapy devices on skin temperatures and compression. A crossover-designed study performed in a university research laboratory was conducted. Each treatment condition was applied to the lateral ankle for 30 min on different days. HyperIce`s colder temperatures over the lateral ankle (p < .0001) would make it the treatment choice for immediate care of ankle lateral ligament injuries, but is limited due its size for larger injuries.